Vocational Guidance and Pre-Profile Training of Schoolchildren with Disabilities: An Analysis of Pedagogical Attitudes and Practices - Zulfia , Movkebayeva; Aitolkyn , Duzelbayeva; Dana , Khamitova; Malika , Usenova; Alibek , Zhigitov; Duzelbayeva, Aitolkyn (Qubahan Academic Journal, 2026)
This article addresses the problem of preparing upper secondary school students with disabilities for subsequent professional and vocational activities, with a particular focus on teachers’ views and attitudes toward the necessity of career guidance and preparatory work aimed at developing initial professional competencies, including personal competencies, among students with disabilities already at the senior school level. Despite significant policy measures undertaken by the state in the field of vocational training and retraining of persons with disabilities—such as the introduction of career guidance teachers in schools, the gradual increase in quotas for specialized workplaces at Kazakhstani enterprises (ranging from 2% to 4% of total jobs), the implementation of subsidies for employers to cover costs associated with equipping specialized workplaces for employees with disabilities, the training of specialized staff in employment centers, and the organization of vocational training and retraining courses—a relatively low rate of permanent employment (39%) persists. Drawing on Bronfenbrenner’s ecological systems theory, the study examines the role of the mesosystem (schools and other educational institutions) and the exosystem (adult social organizations) in the process of pre-profile preparation of students with disabilities for future professional activity, as well as opportunities to enhance their impact. The aim of the study is to identify key practical challenges in creating conditions for the development of initial professional competencies among students with disabilities and to propose new approaches to improving pre-profile training in schools. The methodology includes a systematic review of recent academic and policy sources, as well as an analysis of survey results from teachers working in schools that provide education for students with disabilities. The study concludes with recommendations for policymakers, educators, and vocational institutions on implementing a system of career guidance and pre-profile training for students with disabilities, emphasizing the importance of initiating such activities as early as possible, as they contribute to future professional self-determination, effective employment, and financial self-sufficiency of this population.